Transient T3 toxicosis associated with Hashimoto's disease. Issue 1 (2nd January 2019) - Jaroudi, Sarah; Gavin, Meredith; Boylan, Kathryn; Peiris, Alan N.
Abstract: In its early course, Hashimoto's disease may present as thyrotoxicosis (Hashitoxicosis). This usually manifests as elevated free T4 and suppressed thyroid-stimulating hormone (TSH). We report the unusual occurrence of an elevated T3 level in a patient with Hashimoto's disease. A 27-year-old woman presented with an incidental finding of elevated free T3 levels, normal free T4 levels, and low TSH levels, which were confirmed with follow-up testing. Her only medication was a birth control pill. There was no family history of thyroid disease. Physical examination was normal. She tested positive for thyroid peroxidase and thyroglobulin antibodies. Thyroid heterogeneity was noted on ultrasound. Two months later, her TSH, free T3, and free T4 were normal and remained normal on subsequent testing. No treatment was administered due to spontaneous resolution of her T3 toxicosis. This case highlights a novel presentation of T3 toxicosis in the setting of Hashimoto's disease with spontaneous resolution.